Understanding Organizational Citizenship Behaviour through Organizational Justice and its Consequences among Vietnamese’s Universities Employees - Phuong Ngoc Duy Nguyen; Dong Nguyen Thanh Le (Emerging Science Journal, 2023)
This paper aims to investigate the impact of organizational justice components on job satisfaction, organizational commitment, and organizational citizenship behaviours (OCB) of employees in the higher education sector of Vietnam. Although many research studies have been conducted in organizations on the topics of organizational justice, as well as organizational commitment, and organizational citizenship behaviour, there is a shortage of these topics in higher education institutions as well as in Asian context. Therefore, this article attempts to fill this literature gap. A total of 317 employees from various universities in Vietnam participated in this study, and a self-administered survey was conducted, which was modified based on suggestions from the universities' management team following interviews. The collected data were analyzed using the partial least squares structural equation modeling (PLS-SEM) technique. The results showed that procedural justice and interactional justice had a significant impact on both job satisfaction and organizational commitment, while distributive justice only affected job satisfaction. Furthermore, the study found that job satisfaction and organizational commitment significantly affected OCB. However, this study had a limitation in terms of the narrow sample size, which only included participants from universities. Future studies should broaden the sample size to include participants from vocational colleges. On paper, the study shows the effects of organizational justice on OCB through the mediating roles of individual work outputs, which received inadequate attention in previous studies. Doi: 10.28991/ESJ-2023-SIED2-08 Full Text: PDF